Square diaphragm CMUT capacitance calculation using a new deflection shape function - Rahman, Md. Mosaddequr; Chowdhury, Sazzadur Tanvir Ur Rahman (© 2011 Hindawi Publishing Corporation, 2016)
This article was published in the Journal of Sensors [© 2011 Md Mosaddequr Rahman and Sazzadur Chowdhury.] and the definite version is available at: http://doi.org/10.1155/2011/581910 The Article's website is at: https://www.hindawi.com/journals/js/2011/581910/